Non-intumescent fireproof coating, preparation method and application thereof

CN118909469BActive Publication Date: 2026-10-23SHENZHEN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411148586.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2026-10-23
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

目前,FRP材料已经广泛地用于建筑加固领域,但与之相匹配的防火涂料的研究明显滞后

Benefits of technology

[0026]本发明提供的非膨胀型防火涂料形成的涂层含有三种尺寸的孔,有利于隔热性能的提升。首先偏高岭土、粉煤灰与激发剂反应生成的地聚物胶凝材料自身就具有大量纳米级的凝胶孔,并且吸附了一定量的自由水,高温下蒸发吸收热量有利于隔热。在涂层中加入了空心玻璃微珠,其导热系数较低,加入空心玻璃微珠可以在涂层中引入微米级的孔从而提高涂层隔热性能,此外还可以提高涂层的流动性。在涂层中加入发泡剂,从而在涂层中形成了微米甚至是毫米级的孔,发泡剂不仅可以引入气孔提高隔热性能,同时还可以减少制备时的用水量。阻燃剂受热分解,可以吸热,降低建筑构件的升温趋势,也有利于提高涂层的隔热性能,使其能够更好地保护FRP加固体系,有利于FRP加固体系在火灾下继续发挥加固作用,不至于在火灾发生后较短时间内就发生破坏。这为火灾下人员逃生以及救援提供更充足的时间,可有效降低火灾带来的危害及损失。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005002932700000081
    Figure BDA0005002932700000081
  • Figure BDA0005002932700000101
    Figure BDA0005002932700000101
  • Figure HDA0005002932710000011
    Figure HDA0005002932710000011
Patent Text Reader

Abstract

The application belongs to the technical field of fireproof materials, and particularly relates to a non-intumescent fireproof coating as well as a preparation method and application thereof. The preparation raw materials of the non-intumescent fireproof coating include a binder, a heat insulation filler, a flame retardant, a fiber, an additive and water. The binder includes metakaolin, fly ash and an activator. The heat insulation filler includes expanded vermiculite, vitrified microbeads, sepiolite and hollow glass microbeads. The flame retardant includes aluminum hydroxide and magnesium hydroxide. The fiber includes glass fiber and / or carbon fiber. The additive includes a foaming agent, a thickening agent, a foam stabilizer and an acrylic emulsion. The coating formed by the non-intumescent fireproof coating has excellent heat insulation performance, can be applied as a fireproof coating of a fiber reinforced polymer (FRP), and can effectively protect the FRP reinforcement system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fireproof materials technology, specifically relating to a non-intumescent fireproof coating, its preparation method, and its application. Background Technology

[0002] In recent years, fiber-reinforced polymer (FRP) composites have become a popular reinforcement material due to their advantages such as lightweight, high strength, good durability, and convenient construction. Although FRP bonding reinforcement has many advantages, it also has a significant drawback: extremely poor high-temperature resistance. In the construction industry, most adhesives used to bond FRP materials are epoxy resin-based polymers. Some studies have shown that the properties of these adhesives deteriorate significantly around 75℃, resulting in poor fire resistance of unprotected FRP-reinforced concrete components in a fire, making it difficult to meet the corresponding fire resistance requirements and posing a significant fire safety hazard to such structures. Currently, fire protection for FRP-reinforced structures mainly involves fire-resistant boards or fire-retardant coatings to ensure that the reinforced structure meets the requirements of relevant standards. Non-intumescent fire-retardant coatings are the most widely used. Although the fire resistance limit of the structure can meet the standards under the protection of fire-retardant coatings, their protective effect on the FRP adhesive is not ideal. At high temperatures, the temperature at the FRP site exceeds 100℃ in a very short time. At this temperature, the mechanical properties of the epoxy resin decrease significantly, and it loses its ability to transmit force. This indicates that fire-retardant coatings actually protect reinforced concrete, slowing down the degradation of its properties and thus extending the structure's fire resistance limit. However, this is not suitable for FRP reinforcement systems. Currently, FRP materials are widely used in building reinforcement, but research on matching fire-retardant coatings is significantly lagging behind. Summary of the Invention

[0003] In view of this, the purpose of the present invention is to provide a non-intumescent fire-retardant coating, its preparation method and application. The coating formed by the non-intumescent fire-retardant coating provided by the present invention has excellent thermal insulation properties and can be used as a fire-retardant coating for fiber reinforced polymer (FRP) composites.

[0004] To achieve the above objectives, the present invention provides the following technical solution:

[0005] This invention provides a non-intumescent fire-retardant coating, the raw materials of which include binder, heat-insulating filler, flame retardant, fiber, additives and water:

[0006] The binder includes metakaolin, fly ash, and an activator;

[0007] The thermal insulation filler includes expanded vermiculite, vitrified microspheres, sepiolite, and hollow glass microspheres;

[0008] The flame retardant includes aluminum hydroxide and magnesium hydroxide;

[0009] The fibers include glass fibers and / or carbon fibers;

[0010] The additives include foaming agents, thickeners, foam stabilizers, and acrylic emulsions.

[0011] Preferably, the hollow glass microspheres include two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm; the volume ratio of the two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm is 7:3.

[0012] Preferably, the mass of the flame retardant is 2.3 to 8.2% of the mass of the non-intumescent fire-retardant coating; and the mass ratio of aluminum hydroxide to magnesium hydroxide is 1.5 to 2.5:1.

[0013] Preferably, the foaming agent comprises sodium α-olefin sulfonate.

[0014] Preferably, the foam stabilizer comprises calcium stearate and / or a commercially available powdered foam stabilizer.

[0015] Preferably, the thickener comprises sodium carboxymethyl cellulose and / or cellulose ether.

[0016] Preferably, the mass ratio of metakaolin to fly ash is 5-7:3-5.

[0017] This invention also provides a method for preparing the non-intumescent fire-retardant coating described above, comprising the following steps:

[0018] The binder (excluding the activator), the heat-insulating filler (excluding hollow glass microspheres), and the flame retardant are first mixed to obtain the base material;

[0019] The base material, foaming agent, thickener, and foam stabilizer are mixed a second time to obtain a dry material;

[0020] The dry material is mixed with hollow glass microspheres in a third mixing process, and then an activator, acrylic emulsion and water are added for a fourth mixing process to obtain a mixture.

[0021] The mixture and fiber are mixed and dispersed to obtain a non-intumescent fire-retardant coating.

[0022] The present invention also provides the application of the non-intumescent fire-retardant coating described in the above technical solution or the non-intumescent fire-retardant coating prepared by the preparation method described in the above technical solution in the fire protection of fiber-reinforced composite materials.

[0023] The present invention also provides a method for preparing a non-intumescent fire-retardant coating, comprising the following steps: applying a non-intumescent fire-retardant coating onto the surface of a fiber-reinforced composite material and then curing it to obtain a non-intumescent fire-retardant coating;

[0024] The non-intumescent fire-retardant coating is the non-intumescent fire-retardant coating described in the above technical solution or the non-intumescent fire-retardant coating prepared by the preparation method described in the above technical solution.

[0025] This invention provides a non-intumescent fire-retardant coating, the raw materials of which include a binder, a heat-insulating filler, a flame retardant, fibers, additives, and water: the binder includes metakaolin, fly ash, and an activator; the heat-insulating filler includes expanded vermiculite, vitrified microspheres, sepiolite, and hollow glass microspheres; the flame retardant includes aluminum hydroxide and magnesium hydroxide; the fibers include glass fibers and / or carbon fibers; and the additives include a foaming agent, a thickener, a foam stabilizer, and an acrylic emulsion.

[0026] The non-intumescent fire-retardant coating provided by this invention forms a coating with pores of three sizes, which is beneficial to improving thermal insulation performance. Firstly, the geopolymer cementitious material generated by the reaction of metakaolin, fly ash, and activator itself has a large number of nanoscale gel pores and adsorbs a certain amount of free water. Its evaporation and heat absorption at high temperatures are beneficial for thermal insulation. Hollow glass microspheres are added to the coating. These microspheres have a low thermal conductivity, and their addition introduces micron-sized pores into the coating, thereby improving its thermal insulation performance and also increasing its fluidity. A foaming agent is added to the coating, forming micron- or even millimeter-sized pores. The foaming agent not only introduces pores to improve thermal insulation performance but also reduces the amount of water used in preparation. The flame retardant decomposes upon heating, absorbing heat and reducing the temperature rise of building components, which also helps improve the coating's thermal insulation performance. This allows the coating to better protect the FRP reinforcement system, enabling it to continue its reinforcing function under fire and preventing rapid damage after the fire starts. This provides more time for escape and rescue during a fire, effectively reducing the harm and losses caused by the fire. Attached Figure Description

[0027] Figure 1 This is a diagram of a compression test.

[0028] Figure 2 This is a diagram of a flexural strength test.

[0029] Figure 3 This is a diagram of the bond strength test under direct tension.

[0030] Figure 4 This is a water resistance test diagram;

[0031] Figure 5 This is a schematic diagram of a fire resistance performance test.

[0032] Figure 6 The diagram shows the fire resistance performance of the non-intumescent fire-retardant coating prepared in Example 1. Detailed Implementation

[0033] This invention provides a non-intumescent fire-retardant coating, the raw materials of which include binder, heat-insulating filler, flame retardant, fiber, additives and water:

[0034] The binder includes metakaolin, fly ash, and an activator;

[0035] The thermal insulation filler includes expanded vermiculite, vitrified microspheres, sepiolite, and hollow glass microspheres;

[0036] The flame retardant includes aluminum hydroxide and magnesium hydroxide;

[0037] The fibers include glass fibers and / or carbon fibers;

[0038] The additives include foaming agents, thickeners, foam stabilizers, and acrylic emulsions.

[0039] Unless otherwise specified, the present invention does not have special requirements on the source of the raw materials used in the preparation, and commercially available products well known to those skilled in the art can be used.

[0040] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include a binder. In this invention, the binder includes metakaolin, fly ash, and an activator.

[0041] In this invention, the particle size of the metakaolin is preferably 0.4–200 μm, more preferably D50 particle size = 9.1 μm; the particle size of the fly ash is preferably 0.32–317 μm, more preferably D50 particle size = 5.2 μm; the activator is preferably a water glass activator; the water glass activator is preferably a mixed solution of sodium silicate and sodium hydroxide; the modulus of the activator is preferably 1.2–2 M, more preferably 1.3–1.6 M.

[0042] In this invention, the preferred mass ratio of metakaolin to fly ash is 5-7:3-5, more preferably 7:3; the preferred mass ratio of metakaolin to activator is 70:123-134, more preferably 70:134; and the preferred mass of the binder is 53.1-65.4% of the mass of the non-intumescent fireproof coating, more preferably 53.6-55%.

[0043] In this invention, the binder preferably further comprises: redispersible latex powder and / or polyvinyl alcohol powder, more preferably redispersible latex powder and polyvinyl alcohol powder; the particle size of the redispersible latex powder is preferably 1-7 μm, more preferably 3-5 μm; the particle size of the polyvinyl alcohol powder is preferably 120 mesh; the number average molecular weight of the polyvinyl alcohol powder is preferably 72600-81400, more preferably 80000; the mass ratio of metakaolin to redispersible latex powder is preferably 70:0-5, more preferably 70:2-5; the mass ratio of metakaolin to polyvinyl alcohol powder is preferably 70:0-1.5, more preferably 70:0.5-1.5.

[0044] In this invention, the geopolymer cementitious material generated by the reaction of metakaolin, fly ash, and activator possesses numerous nanoscale gel pores and adsorbs a certain amount of free water. Its evaporation and heat absorption at high temperatures are beneficial for thermal insulation. Redispersible latex powder and polyethylene can enhance the adhesion strength of the coating.

[0045] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include heat-insulating fillers. In this invention, the heat-insulating fillers include expanded vermiculite, vitrified microspheres, sepiolite, and hollow glass microspheres.

[0046] In this invention, the particle size of the expanded vermiculite is preferably 68–564 μm, more preferably D50 particle size = 226.6 μm; the particle size of the vitrified microspheres is preferably 1–2 mm; the particle size of the sepiolite is preferably 300–400 μm, more preferably 350–400 μm; the hollow glass microspheres preferably include two types: D50 particle size = 65 μm and D50 particle size = 40 μm; the volume ratio of the two types of hollow glass microspheres with D50 particle size = 65 μm and D50 particle size = 40 μm is preferably 7:3; the wall thickness of the hollow glass microspheres is preferably 1–3 μm, more preferably 2 μm; the true density of the hollow glass microspheres with D50 particle size = 40 μm is preferably 0.59–0.63 g / cm³. 3 More preferably 0.6 g / cm³ 3 The preferred bulk density is 0.33–0.36 g / cm³. 3 More preferably 0.35 g / cm³ 3 The preferred true density of hollow glass microspheres with a D50 particle size of 65 μm is 0.19–0.23 g / cm³. 3 More preferably 0.2 g / cm³ 3 The preferred bulk density is 0.09–0.12 g / cm³. 3 More preferably 0.1 g / cm³ 3 .

[0047] In this invention, the preferred mass ratio of expanded vermiculite to hollow glass microspheres is 43.8:17.4–21.6, more preferably 43.8:17.4; the preferred mass ratio of vitrified microspheres to hollow glass microspheres is 14.6:21.6 or 21.9:17.4, more preferably 21.9:17.4; the preferred mass ratio of sepiolite to hollow glass microspheres is 15.4:17.4–21.6, more preferably 15.4:17.4; and the preferred mass of the heat-insulating filler is 13.4–22.8% of the mass of the non-intumescent fire-retardant coating, more preferably 15–22.5%.

[0048] In this invention, expanded vermiculite and vitrified microspheres have low densities, effectively reducing the density of the fire-retardant coating. Furthermore, expanded vermiculite has a hollow internal structure and a layered structure, providing excellent thermal insulation properties. Vitrified microspheres also have a porous microstructure, similarly enhancing the thermal insulation performance of the fire-retardant coating. Both materials have micron-sized pores. Sepiolite contains a significant amount of fibrous, hydrated magnesium silicate with a large aspect ratio; at high temperatures, it absorbs heat through water evaporation, thus slowing heat conduction. Additionally, sepiolite also has a certain toughening effect.

[0049] In this invention, hollow glass microspheres have a low thermal conductivity. Adding hollow glass microspheres can introduce micron-sized pores into the coating, thereby improving the thermal insulation performance of the coating. In addition, it can also improve the working performance of the coating.

[0050] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include a flame retardant. In this invention, the flame retardant includes aluminum hydroxide and magnesium hydroxide; the mass of the flame retardant is preferably 2.3-8.2% of the mass of the non-intumescent fire-retardant coating, more preferably 3-4.5%; the mass ratio of aluminum hydroxide to magnesium hydroxide is preferably 1.5-2.5:1, more preferably 2.08:1.

[0051] In this invention, the flame retardant decomposes upon heating, which can absorb heat, reduce the temperature rise of building components, and also improve the thermal insulation performance of the coating.

[0052] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include fibers. In this invention, the fibers preferably include glass fibers and / or carbon fibers, more preferably glass fibers; the length of the fibers is preferably 6–12 mm, more preferably 6 mm; the diameter of the fibers is preferably 5–20 μm, more preferably 8–15 μm; the mass of the fibers is preferably 0.22–0.82% of the mass of the non-intumescent fire-retardant coating, more preferably 0.25–0.45%. The role of the fibers in this invention is to increase the toughness of the coating and reduce the risk of cracking.

[0053] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include additives. In this invention, the additives include foaming agents, thickeners, foam stabilizers, and acrylic emulsions.

[0054] In this invention, the foaming agent preferably comprises sodium α-olefin sulfonate; the foam stabilizer preferably comprises calcium stearate and / or a commercial powdered foam stabilizer, more preferably calcium stearate and a commercial powdered foam stabilizer; the mass ratio of calcium stearate to the commercial powdered foam stabilizer is preferably 1:2 to 0.5, more preferably 1:1; the thickener preferably comprises sodium carboxymethyl cellulose and / or cellulose ether, more preferably sodium carboxymethyl cellulose and cellulose ether; the mass ratio of sodium carboxymethyl cellulose to cellulose ether is preferably 1:2 to 0.5, more preferably 1:1. In this invention, the manufacturer of the commercial powdered foam stabilizer is Luoyang Tongrun Nanotechnology Co., Ltd., and the model is: Lightweight Partition Board Foam Stabilizer.

[0055] In this invention, the foam stabilizer disperses at the gas-liquid interface of the bubbles, which is beneficial to bubble stability and prevents bubble collapse. Furthermore, the foam stabilizer can optimize the bubble structure. The thickener increases the viscosity of the coating, refines the pores formed by the foaming agent, makes the coating easier to apply, and improves its resistance to sagging and dripping.

[0056] In this invention, the preferred mass ratio of the foaming agent to the thickener is 0.1–0.3:0.07, more preferably 0.2:0.07; the preferred mass ratio of the foaming agent to the foam stabilizer is 0.1–0.3:0.5, more preferably 0.2:0.5; the preferred mass ratio of the foaming agent to the acrylic emulsion is 0.1–0.3:1, more preferably 0.2:1; and the preferred mass of the additives is 0.37–0.87% of the mass of the non-intumescent fire-retardant coating, more preferably 0.4–0.6%.

[0057] In this invention, the foaming agent can form micron or even millimeter-sized pores in the coating. The foaming agent can not only introduce pores to improve thermal insulation performance, but also reduce the amount of water used in the preparation process.

[0058] The raw materials for preparing the non-intumescent fire-retardant coating provided by this invention include water. In this invention, the mass of the water is preferably 14.3–22.1% of the mass of the non-intumescent fire-retardant coating, more preferably 15–18.1%.

[0059] The non-intumescent fire-retardant coating provided by this invention is based on a geopolymer in which various lightweight heat-insulating fillers and flame retardants are dispersed, and the bonding strength is improved by adding redispersible latex powder and polyethylene. Furthermore, various additives are added to improve workability and durability.

[0060] This invention optimizes the dosage of various raw materials in the preparation of non-intumescent fire-retardant coatings, resulting in a coating containing pores of multiple sizes, which is beneficial to improving thermal insulation performance.

[0061] This invention also provides a method for preparing the non-intumescent fire-retardant coating described above, comprising the following steps:

[0062] The binder (excluding the activator), the heat-insulating filler (excluding hollow glass microspheres), and the flame retardant are first mixed to obtain the base material;

[0063] The base material, foaming agent, thickener, and foam stabilizer are mixed a second time to obtain a dry material;

[0064] The dry material is mixed with hollow glass microspheres in a third mixing process, and then an activator, acrylic emulsion and water are added in a fourth mixing process to obtain a mixture.

[0065] The mixture and fiber are mixed and dispersed to obtain a non-intumescent fire-retardant coating.

[0066] In this invention, the first mixing is preferably carried out under low-speed stirring; the speed of the low-speed stirring is preferably 130-150 rpm, more preferably 140 rpm; the time of the first mixing is preferably 3-5 min, more preferably 3 min.

[0067] In this invention, the second mixing is preferably carried out under low-speed stirring; the stirring speed is preferably 130-150 rpm, more preferably 140 rpm; the mixing time is preferably 1-3 min, more preferably 1 min; and the equipment used for the second mixing is preferably a mixing pot. During the second mixing process, this invention preferably uses a cover plate to shield the top of the mixing pot to prevent the added additives from splashing out.

[0068] In this invention, the third mixing is preferably performed by first manually stirring, followed by low-speed stirring; the low-speed stirring rate is preferably 130-150 rpm, more preferably 140 rpm; the low-speed stirring time is preferably 1 minute; and the equipment used for the third mixing is preferably a mixing pot. During the third mixing process, the top of the mixing pot is preferably covered with a lid. Because the hollow glass microspheres have extremely low density, they are first dispersed in the dry material by manual stirring, and then low-speed stirring is performed.

[0069] In this invention, the acrylic emulsion and water are preferably used in the form of a mixture of acrylic emulsion and water; the method for preparing the mixture of acrylic emulsion and water is preferably to mix and stir the acrylic emulsion and water evenly; the stirring speed is preferably 30 to 50 rpm, more preferably 30 rpm.

[0070] In this invention, the fourth mixing is preferably performed by first stirring at low speed and then stirring at high speed; the speed of the low-speed stirring is preferably 130-150 rpm, more preferably 140 rpm; the time of the low-speed stirring is preferably 1-2 min, more preferably 1 min; the speed of the high-speed stirring is preferably 270-300 rpm, more preferably 290 rpm; the time of the high-speed stirring is preferably 2-3 min, more preferably 2 min; the equipment used for the fourth mixing is preferably a mixing pot; after the high-speed stirring, this invention preferably uses a spatula to scrape the unevenly mixed material on the pot wall and blades into the already evenly mixed material in the mixing pot. In the fourth mixing process, the first low-speed stirring ensures sufficient contact between the dry material and the liquid, and also prevents the material from splashing out during high-speed stirring.

[0071] In this invention, the preferred method for dispersing the mixture and fibers is as follows: the fibers are gradually added to the mixture under low-speed stirring, followed by high-speed stirring for dispersion; the gradual addition is preferably done in small amounts multiple times; the low-speed stirring rate is preferably 130-150 rpm, more preferably 140 rpm; the high-speed stirring rate is preferably 270-300 rpm, more preferably 290 rpm; the high-speed stirring time is preferably 3-5 min, more preferably 5 min; this invention preferably involves manually dispersing any clumps of fibers before adding them to the mixture to prevent fiber clumping.

[0072] The present invention also provides the application of the non-intumescent fire-retardant coating described in the above technical solution or the non-intumescent fire-retardant coating prepared by the preparation method described in the above technical solution in the fire protection of fiber-reinforced composite materials.

[0073] The present invention also provides a non-intumescent fireproof coating, comprising the following steps: applying a non-intumescent fireproof coating to the surface of a fiber-reinforced composite material and then curing it to obtain a non-intumescent fireproof coating;

[0074] The non-intumescent fire-retardant coating is the non-intumescent fire-retardant coating described in the above technical solution or the non-intumescent fire-retardant coating prepared by the preparation method described in the above technical solution.

[0075] In this invention, the coating method is preferably manual application or spraying, more preferably manual application; the curing temperature is preferably 25–35°C, more preferably 25–30°C; the curing humidity is preferably 70–85%, more preferably 70–80%; and the curing time is preferably 14–28 days, more preferably 28 days. This invention does not impose a specific limitation on the thickness of the non-intumescent fire-retardant coating; it can be determined according to the requirements of the application scenario. In an example application of this invention, the thickness of the non-intumescent fire-retardant coating is 25 mm.

[0076] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.

[0077] Example 1

[0078] The raw materials for preparing the non-intumescent fire-retardant coating described in Example 1 are shown in Table 1:

[0079] Table 1. Raw materials for preparing the non-intumescent fire-retardant coating described in Example 1.

[0080]

[0081] Among them, the D50 particle size of metakaolin is 9.1 μm; the D50 particle size of fly ash is 5.2 μm; the water glass activator is a mixed solution of sodium silicate and sodium hydroxide; the modulus of the water glass activator is 1.6M; the particle size of redispersible latex powder is 5 μm; the particle size of polyvinyl alcohol powder is 120 mesh, and the number average molecular weight of polyvinyl alcohol powder is 80,000; the D50 particle size of expanded vermiculite is 226.6 μm; and the particle size of vitrified microspheres is... The diameter is 1–2 mm; the sepiolite particle size is 350–400 μm; the hollow glass microspheres are composed of two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm, with a volume ratio of 7:3. The wall thickness of the hollow glass microspheres is 2 μm, and the actual density of the hollow glass microspheres with a D50 particle size of 40 μm is 0.6 g / cm³. 3 The bulk density is 0.35 g / cm³. 3 The true density of hollow glass microspheres with a D50 particle size of 65 μm is 0.2 g / cm³. 3 The bulk density is 0.1 g / cm³. 3 The glass fiber has a length of 6mm and a diameter of 15μm; the foaming agent is sodium α-olefin sulfonate; the foam stabilizer is calcium stearate and commercial powdered foam stabilizer (Luoyang Tongrun Nanotechnology Co., Ltd., model: lightweight partition board foam stabilizer) in a mass ratio of 1:1; the thickener is sodium hydroxymethyl cellulose and cellulose ether in a mass ratio of 1:1.

[0082] The preparation method of the non-intumescent fire-retardant coating is as follows:

[0083] Step 1: First, add the binder (excluding water glass activator), the heat insulation filler (excluding hollow glass microspheres), and the flame retardant to the mixing pot for dry mixing. Stir at a low speed of 140 rpm for 3 minutes to obtain the base material.

[0084] Step 2: Add foaming agent, thickener and foam stabilizer to the base material, and continue to stir at a low speed of 140 rpm for 1 minute. The top of the mixing pot should be covered with a cover plate to prevent the added additives from splashing out, and dry material is obtained.

[0085] Step 3: Add hollow glass microspheres to the dry material. Due to their extremely low density, first use manual stirring to disperse them in the dry material, then stir at a low speed of 140 rpm for 1 minute. Again, it is necessary to cover the mixture with a cover plate to obtain the hollow glass microsphere mixture.

[0086] Step 4: Mix the acrylic emulsion with water at 30 rpm until homogeneous to obtain a mixture of acrylic emulsion and water;

[0087] Step 5: Add the mixture of water glass activator, acrylic emulsion and water to the hollow glass microsphere mixture in the mixing pot. First, stir at a low speed of 140 rpm for 1 minute to ensure that the dry material and liquid are in full contact, and at the same time to prevent the material from splashing out during high-speed stirring. Then, stir at a high speed of 290 rpm for 2 minutes. Use a spatula to scrape the unevenly mixed material on the pot wall and blades into the already evenly mixed material in the mixing pot to obtain the mixture.

[0088] Step 6: Add glass fiber to the mixture using a low-speed stirring mode of 140 rpm. When adding glass fiber, add it in small amounts multiple times, and manually disperse any clumps of fiber before adding it. Then, stir again at a high speed of 290 rpm for 5 minutes to fully disperse the fiber in the slurry, thus obtaining a non-intumescent fire-retardant coating.

[0089] Example 2

[0090] The difference from Example 1 is that the amount of heat-insulating filler in Example 1 is replaced with 13.4% of the mass of the non-intumescent fire-retardant coating.

[0091] Example 3

[0092] The difference from Example 1 is that the glass fiber in Example 1 is replaced with carbon fiber.

[0093] Comparative Example 1

[0094] The difference from Example 1 is that hollow glass microspheres are not added.

[0095] Comparative Example 2

[0096] The difference from Example 1 is that no foaming agent is added.

[0097] Comparative Example 3

[0098] The difference from Example 1 is that no flame retardant is added.

[0099] Application Example 1

[0100] The non-intumescent fire-retardant coating prepared in Example 1 was applied manually to the surface of the fiber-reinforced composite material reinforcement. After curing at 25°C and 70% humidity for 28 days, a non-intumescent fire-retardant coating with a thickness of 25 mm was obtained.

[0101] Application Example 2

[0102] The difference from Application Example 1 is that the non-intumescent fire retardant coating prepared in Example 1 is replaced with the non-intumescent fire retardant coating prepared in Example 2, and the rest is the same as Application Example 1.

[0103] Application Example 3

[0104] The difference from Application Example 1 is that the non-intumescent fire retardant coating prepared in Example 1 is replaced with the non-intumescent fire retardant coating prepared in Example 3, and the rest is the same as Application Example 1.

[0105] Comparative Application Example 1

[0106] The difference from Application Example 1 is that the non-intumescent fire retardant coating prepared in Example 1 is replaced with the non-intumescent fire retardant coating prepared in Comparative Example 1, and the rest is the same as Application Example 1.

[0107] Comparative Application Example 2

[0108] The difference from Application Example 1 is that the non-intumescent fire retardant coating prepared in Example 1 is replaced with the non-intumescent fire retardant coating prepared in Comparative Example 2, and the rest is the same as Application Example 1.

[0109] Comparative Application Example 3

[0110] The difference from Application Example 1 is that the non-intumescent fire retardant coating prepared in Example 1 is replaced with the non-intumescent fire retardant coating prepared in Comparative Example 3, and the rest is the same as Application Example 1.

[0111] Performance testing

[0112] (1) The density of the non-intumescent fire-retardant coatings prepared in Examples 1 and 2 was tested. The specific test method was as follows: a 50mm×50mm×50mm cube was used to measure the dry density. After curing for 28 days, the specimen was placed in a drying oven at 105℃ and dried to constant weight. Then, the side length b was measured with vernier calipers, and the mass m was weighed. The density was calculated using the following formula:

[0113]

[0114] The non-intumescent fire-retardant coatings prepared in Examples 1 and 2 of this invention form coatings with densities of 560 kg / m³, respectively. 3 and 730kg / m 3 .

[0115] (2) The compressive strength of the coating formed by the non-intumescent fire-retardant coating prepared in Example 1 was tested. Specifically, the compressive strength test was conducted using a 50mm×50mm×50mm cube. After curing for 28 days, the cube was placed in a drying oven at 60℃ for 12 hours. Then, a 5t MTS testing machine was used for the compressive strength test at a loading rate of 200N / min. The compressive strength test was performed as follows: Figure 1 As shown.

[0116] The non-intumescent fire-retardant coating prepared by this invention forms a coating with a compressive strength of 0.66 MPa.

[0117] (3) The flexural strength of the non-intumescent fire-retardant coating prepared in Example 1 was tested. Specifically, a 160mm×40mm×40mm specimen was used for the flexural strength test. After curing for 28 days, the specimen was placed in a drying oven at 60℃ for 12 hours. Then, a standard compressive and flexural strength testing machine was used for the flexural strength test. The loading rate was 10mm / min. The flexural strength test results are as follows: Figure 2 As shown.

[0118] The non-intumescent fire-retardant coating prepared by this invention forms a coating with a flexural strength of 0.49 MPa.

[0119] (4) Bond strength: The bond strength in this invention refers to the bond strength between the non-intumescent fireproof coating prepared in Example 1 and the cement mortar substrate. A 70mm × 70mm × 20mm cement mortar test block was used, with a 5mm thick coating applied to its surface. After curing for 28 days, a direct tensile test was conducted to determine the bond strength. The direct tensile test results are as follows: Figure 3 As shown.

[0120] The non-intumescent fire-retardant coating prepared by this invention forms a coating with an adhesion strength of 0.2 MPa.

[0121] (5) Water resistance: A fiber-reinforced low-alkalinity cement slab with dimensions of 150mm × 70mm × 6mm was used as the base plate. A 5mm thick layer of the non-intumescent fire-retardant coating prepared in Example 1 was applied to the surface of the base plate to form a coating. After curing for 28 days, the edges and back of the specimen were sealed with a mixture of paraffin and rosin (mass ratio 1:1). Then, 2 / 3 of the specimen was immersed in water. After soaking for 28 days, no cracks appeared on the surface. The water resistance test results were as follows. Figure 4 As shown.

[0122] (6) High and low temperature cycling: The specimens used for high and low temperature resistance test are the same as those used for water resistance test. The cycling process is as follows: store in an environment of -20℃±2℃ for 3 hours, and then store in an environment of 50℃±2℃ for 3 hours. Repeat the above process 20 times.

[0123] The non-intumescent fire-retardant coating prepared by this invention did not crack on the surface after 20 cycles.

[0124] (7) Fire resistance performance: A simplified version of the fire resistance limit test was adopted. The test substrate was a 150mm×150mm×25mm concrete block, and a 25mm thick layer of the non-intumescent fire-retardant coating prepared in Example 1 was applied to the surface. The surface was then smoothed and cured for 28 days. The test equipment used was a multi-functional box furnace purchased from the laboratory, which can achieve a heating process close to that described by the ISO standard heating curve. During the test, the coating surface was placed facing the inside of the furnace, directly exposed to the high-temperature environment. The temperature change at the interface between the coating and the concrete substrate was recorded by thermocouples embedded in the specimen. The test diagram is shown below. Figure 5 As shown, the results are as follows Figure 6 As shown. The furnace temperature refers to the temperature of the high-temperature furnace cavity, which is also the temperature applied to the coating surface. The temperature at the interface between the coating and the substrate is also the temperature of the FRP material, which is attached to the substrate surface.

[0125] The temperature change on the exposed side of the coating was recorded during the fire resistance test. Figure 6 As can be seen, a clear plateau appears in the temperature curve during the early stages of a fire. This is highly beneficial for the FRP reinforcement system to continue its reinforcing function under fire conditions, preventing it from failing shortly after the fire begins. This provides more time for people to escape and for rescue during a fire, effectively reducing the harm and losses caused by the fire.

[0126] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A non-intumescent fire-retardant coating, characterized in that, The raw materials for preparation include binders, heat-insulating fillers, flame retardants, fibers, additives, and water: The binder is composed of metakaolin, fly ash and activator; The thermal insulation filler includes expanded vermiculite, vitrified microspheres, sepiolite, and hollow glass microspheres; The flame retardant includes aluminum hydroxide and magnesium hydroxide; The fibers include glass fibers and / or carbon fibers; The additives include foaming agents, thickeners, foam stabilizers, and acrylic emulsions; The hollow glass microspheres include two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm; the volume ratio of the two types of hollow glass microspheres with a D50 particle size of 65 μm and a D50 particle size of 40 μm is 7:

3. The mass of the flame retardant is 2.3% to 8.2% of the mass of the non-intumescent fire-retardant coating; The mass ratio of metakaolin to fly ash is 7:

3.

2. The non-intumescent fire-retardant coating according to claim 1, characterized in that, The mass ratio of aluminum hydroxide to magnesium hydroxide is 1.5~2.5:

1.

3. The non-intumescent fire-retardant coating according to claim 1, characterized in that, The foaming agent includes sodium α-olefin sulfonate.

4. The non-intumescent fire-retardant coating according to claim 1, characterized in that, The foam stabilizer includes calcium stearate and / or commercial powdered foam stabilizers.

5. The non-intumescent fire-retardant coating according to claim 1, characterized in that, The thickener includes sodium hydroxymethyl cellulose and / or cellulose ether.

6. The method for preparing the non-intumescent fire-retardant coating according to any one of claims 1 to 5, characterized in that, Includes the following steps: The binder (excluding the activator), the heat-insulating filler (excluding hollow glass microspheres), and the flame retardant are first mixed to obtain the base material; The base material, foaming agent, thickener, and foam stabilizer are mixed a second time to obtain a dry material; The dry material is mixed with hollow glass microspheres in a third mixing process, and then an activator, acrylic emulsion and water are added in a fourth mixing process to obtain a mixture. The mixture and fiber are mixed and dispersed to obtain a non-intumescent fire-retardant coating.

7. The application of the non-intumescent fire-retardant coating according to any one of claims 1 to 5 or the non-intumescent fire-retardant coating prepared by the preparation method according to claim 6 in the fire protection of fiber-reinforced composite materials.

8. A method for preparing a non-intumescent fire-retardant coating, characterized in that, Includes the following steps: After applying a non-intumescent fire-retardant coating to the surface of a fiber-reinforced composite material and then curing it, a non-intumescent fire-retardant coating is obtained. The non-intumescent fire-retardant coating is the non-intumescent fire-retardant coating according to any one of claims 1 to 5 or the non-intumescent fire-retardant coating prepared by the preparation method according to claim 6.

Citation Information

Patent Citations

  • Alkaline ore slag tunnel fireproof coating using composite activator and preparation method thereof

    CN107117878A